Հայերը Թուրքեստանի քաղաքներում - Շագոյան, Անահիտ (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Создание Туркестанского генерал-губернаторства в 1867 г. не только облегчило управление регионом, но и дало возможность развивать его, используя потенциал местного населения, часть которого составляли армяне. Армянское население крупнейших городов Туркестана (Ашхабад, Мерв, Самарканд, Коканд) начиная с XX в. принимало активное участие как в социальной, так и культурной и духовной жизни республики, внося тем самым свой весомый вклад в развитие рассматриваемого региона. Речь идет о создании духовных и образовательных центров и формировании женских благотворительных обществ. In 1867, the creation of the general-governorship of Turkestan not only facilitated the management of the region, but also availed possibilities of its development, using the potential of the local population, the inhabitants of the Empire, in which the Armenians did not stand aside. The Armenian population living in the largest cities of Turkestan (Ashgabat, Merv, Samarkand, Kokand) since the 1980s, took an active part in both the social and cultural-spiritual life of the republic, making a considerable contribution to the development of the region in question through establishing educational and spiritual centres, as well as women's benevolent organizations.
Keywords: Պատմություն